PENGATURAN PENGAWASAN SATUAN POLIS PAMONG PRAJA TERHADAP BANGUNAN LIAR DI RUANG MILIK JALAN (RUMIJA) DI KOTA KUPANG - Baari, Harianto Lele; Stefanus, Kotan Y; Ratu Udju, Hernimus (Petitum Law Journal, 2023)
Public order and public peace are dynamic conditions that allow local governments and communities to carry out their activities in a peaceful, orderly, and orderly manner. Therefore, in order to anticipate the development and dynamics of community activities in line with the demands of the era of globalization and regional autonomy, conducive conditions of regional peace and public order are fundamental needs for the community in an effort to improve the quality of their lives. Thus, the emergence of a skewed image of the figure of the Civil Service and Spatial Planning Police Unit is none other than because the community is often treated to repressive actions, but seems arrogant from the regional apparatus when carrying out its role in maintaining and maintaining security and public order. On the basis of the above, the author raises the main problem as follows: 1) What are the Supervision Arrangements of the Civil Service Police Unit on Illegal Buildings in Road-Owned Space (RUMIJA)? 2)What Are the Factors That Hinder the Supervision of the Civil Service Police Unit on Illegal Buildings in Road-Owned Space (RUMIJA)? This research uses normative-empirical juridical research methods, namely research whose data is directly obtained from the research location of respondents (resource persons) and supported by literature research. The results of this study show that the Regulation and Supervision of the Kupang City Civil Service Police Unit in enforcing Kupang City Regional Regulation Number 9 of 2003 concerning Building Arrangement has not been very good in regulating and supervising or arranging buildings in Kupang City so that people are still found building illegal buildings in road-owned spaces (Rumija), this can be seen from the increasing cases of illegal buildings in Kupang City over the past 3 (three) years. So it can be said that the Regulation and Supervision of the Kupang City Civil Service Police Unit and Kupang City Spatial Planning